Central Bank Independence and Fiscal Policy: Can the Central Bank Restrain Deficit Spending?. Issue 1 (15th July 2015) - Bodea, Cristina; Higashijima, Masaaki
Abstract : Independent central banks prefer balanced budgets due to the long-run connection between deficits and inflation, and can enforce their preference through interest rate increases and denial of credit to the government. This article argues that legal central bank independence (CBI) deters fiscal deficits predominantly in countries with rule of law and impartial contract enforcement, a free press and constraints on executive power. It further suggests that CBI may not affect fiscal deficits in a counter-cyclical fashion, but instead depending on the electoral calendar and government partisanship. The article also tests the novel hypotheses using new yearly data on legal CBI for seventy-eight countries from 1970 to 2007. The results show that CBI restrains deficits only in democracies, during non-election years and under left government tenures.